2016
DOI: 10.3390/microorganisms4030022
|View full text |Cite
|
Sign up to set email alerts
|

A Look inside the Listeria monocytogenes Biofilms Extracellular Matrix

Abstract: Listeria monocytogenes is a foodborne pathogen able to persist in food industry and is responsible for a severe illness called listeriosis. The ability of L. monocytogenes to persist in environments is due to its capacity to form biofilms that are a sessile community of microorganisms embedded in a self-produced matrix of extracellular polymeric substances (EPS’s). In this review, we summarized recent efforts performed in order to better characterize the polymeric substances that compose the extracellular matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 102 publications
(129 reference statements)
1
50
0
1
Order By: Relevance
“…Biofilm formation is often supported by accumulation of food residues in specific niches, like meat choppers or minced meat machines (8). It has been shown that L. monocytogenes is capable to form biofilm on stainless steel and glass or even polyvinyl chloride and polyethylene surfaces (4). The structure of the biofilm shows a great variety, from monolayer of cells to knitted chain network and honeycomb-like structure.…”
Section: Rte Meat Production Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm formation is often supported by accumulation of food residues in specific niches, like meat choppers or minced meat machines (8). It has been shown that L. monocytogenes is capable to form biofilm on stainless steel and glass or even polyvinyl chloride and polyethylene surfaces (4). The structure of the biofilm shows a great variety, from monolayer of cells to knitted chain network and honeycomb-like structure.…”
Section: Rte Meat Production Chainmentioning
confidence: 99%
“…Biofilm forming is influenced by L. monocytogenes factors, such as biofilm-associated protein (Bap), protein SecA2, and flagella, as well as environmental conditions, like temperature and adhesion properties of the surfaces (18). No correlation between L. monocyogenes molecular lineages or serovars and biofilm formation capacity has been observed (4,7,8). Additionally, it has been shown that these bacteria are able to form biofilms with other microorganisms which may be present in the production environment, e.g.…”
Section: Rte Meat Production Chainmentioning
confidence: 99%
“…The ability of bacterial pathogens to remain viable in food production environments, even with the enforcement of stringent hygiene practices, can be in part due to the accumulation of resistance mechanisms (Holah et al, 2002; Tauxe, 2002) and through the protection provided via the formation of biofilms (Borucki et al, 2003; Ryu and Beuchat, 2005; Houdt and Michiels, 2010). Surface-attached biofilms are sessile microbial communities that can be irreversibly attached to a substratum and are enclosed in an extracellular polymeric matrix (Donlan, 2002; Olszewska, 2013; Colagiorgi et al, 2016). Once formed, biofilms can be extremely difficult to remove, leading to contamination of processing equipment (Kumar and Anand, 1998; Tan et al, 2014), food spoilage and consequent economic losses (Brooks and Flint, 2008; Houdt and Michiels, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, changes in biofilm production within L. monocytogenes strains may well be affected by phenotypic heterogeneity (Ackermann, 2015) as a strategy to cope with dynamic environments (such as those found in the fresh produce supply chain). Furthermore, the accessory genome (which was not investigated in this study) of all L. monocytogenes lineages is enriched for cell surface-related genes (den Bakker et al, 2013), the products of which are likely to be involved in the EPS matrix of biofilms (Colagiorgi et al, 2016). Whilst a correlation between lineage and biofilm production (lineage II isolates producing more biofilm has been reported (Borucki et al, 2003)) our results indicate that phylogenetic lineage does not affect biofilm…”
Section: Accepted Manuscriptmentioning
confidence: 46%